The Eye of Saturn's North Polar Vortex: Unexpected Cloud Structures Observed at High Spatial Resolution by Cassini/VIMS. Issue 12 (25th June 2018) - Baines, K. H.; Sromovsky, L. A.; Fry, P. M.; Momary, T. W.; Brown, R. H.; Buratti, B. J.; Clark, R. N.; Nicholson, P. D.; Sotin, C.
Abstract: Near‐infrared spectral maps of Saturn's north polar vortex obtained at high spatial resolution provided by Cassini/Visual Infrared Mapping Spectrometer (VIMS) reveal localized ammonia clouds composed of unusually large particles exceeding 13 μm in radius, the largest cloud particles documented during the Cassini mission. Taken under near‐optimum direct polar lighting and viewing conditions within a month of the summer solstice, these small (~200 km in breadth) discrete clouds are located within the eye of the polar vortex, which otherwise is unusually clear of observable aerosols in reflected sunlight, with total 2‐μm opacity <0.04 versus >1.0 elsewhere on Saturn. The dichotomy of large‐particle condensate cloud features—indicative of convective upwelling—within a large (~ 2000‐km diameter) nearly aerosol‐free region of downwelling characteristic of the core of a polar vortex reveals surprising polar dynamics on Saturn. Plain Language Summary: Saturn's north pole was imaged with unprecedented clarity in over 200 colors during the Grand Finale phase of the Cassini mission, revealing surprising details on the structures of hazes and clouds. A cyclonic vortex caps the pole, extending out about 20° (20, 000 km) in latitude, the largest cyclone known in the solar system. As a cyclone, this is a region of subsidence, where air descends downward. Such air, descending into warmer depths, should be relatively clear of condensate clouds of ammonia—one of the major condensables in Saturn's visible atmosphere—especially in the eye of the polar vortex right at the pole. The new multicolored near‐infrared images obtained by the Visual Infrared Mapping Spectrometer reveal that indeed the polar eye is remarkably devoid of aerosols, having less than 3% of the aerosol content seen anywhere else on Saturn. But surprisingly, ammonia clouds at the edge of the eye—but still within it—are found to be remarkably thick, composed of the largest ammonia ice particles ever seen on Saturn, characteristic of powerful upwelling, not downwelling (subsidence). This conundrum of convection‐style clouds forming in a strongly downwelling region is a shocking mystery left by Cassini in its waning days. Key Points: Cassini mission Grand Finale high‐resolution VIMS spectral images of Saturn's north pole reveal unexpected extremes in cloud structures Cassini/VIMS finds the largest cloud particles yet observed on Saturn, surprisingly within the downwelling polar cyclone North polar cyclone eye has the clearest skies seen on Saturn to ~3 bar, with <3% of the aerosol opacity typically observed elsewhere